Novel azo-peresters radical initiators used for the synthesis of acrylic pressure-sensitive adhesives (eXPRESS Polymer Letters)
Acrylic pressure-sensitive adhesives (PSA) based on two monomers: 2-ethylhexyl acrylate and acrylic acid were synthesized in organic solvent ethyl acetate using AIBN (2, 2'-azo-diisobutyronitrile) and new synthesized azo-peresters as radical initiators. After polymerization the viscosity, molecular weight and polydispersity of synthesized acrylic PSA were evaluated. The novel synthesized radical azo-perester initiators were synthesized, isolated and compared with industrial predominant usable azo-initiator AIBN.